Placozoan fiber cells: mediators of innate immunity and participants in wound healing - Tatiana D. Mayorova (Nature Portfolio, 2021)
Abstract Placozoa is a phylum of non-bilaterian marine animals. These small, flat organisms adhere to the substrate via their densely ciliated ventral epithelium, which mediates mucociliary locomotion and nutrient uptake. They have only six morphological cell types, including one, fiber cells, for which functional data is lacking. Fiber cells are non-epithelial cells with multiple processes. We used electron and light microscopic approaches to unravel the roles of fiber cells in Trichoplax adhaerens, a representative member of the phylum. Three-dimensional reconstructions of serial sections of Trichoplax showed that each fiber cell is in contact with several other cells. Examination of fiber cells in thin sections and observations of live dissociated fiber cells demonstrated that they phagocytose cell debris and bacteria. In situ hybridization confirmed that fiber cells express genes involved in phagocytic activity. Fiber cells also are involved in wound healing as evidenced from microsurgery experiments. Based on these observations we conclude that fiber cells are multi-purpose macrophage-like cells. Macrophage-like cells have been described in Porifera, Ctenophora, and Cnidaria and are widespread among Bilateria, but our study is the first to show that Placozoa possesses this cell type. The phylogenetic distribution of macrophage-like cells suggests that they appeared early in metazoan evolution.